The diurnal cycle of pCO2 in the coastal region of the Baltic Sea - M. Honkanen (Copernicus Publications, 2021)
The direction and magnitude of carbon dioxide fluxes between the atmosphere and the sea are regulated by the gradient in the partial pressure of carbon dioxide (pCO2) across the air–sea interface. Typically, observations of pCO2 at the sea surface are carried out by using research vessels and ships of opportunity, which usually do not resolve the diurnal cycle of pCO2 at a given location. This study evaluates the magnitude and driving processes of the diurnal cycle of pCO2 in a coastal region of the Baltic Sea. We present pCO2 data from July 2018 to June 2019 measured in the vicinity of the island of Utö at the outer edge of the Archipelago Sea, and quantify the relevant physical, biological, and chemical processes controlling pCO2. The highest monthly median of diurnal pCO2 variability (31 µatm) was observed in August and predominantly driven by biological processes. Biological fixation and mineralization of carbon led to sinusoidal diurnal pCO2 variations, with a maximum in the morning and a minimum in the afternoon. Compared with the biological carbon transformations, the impacts of air–sea fluxes and temperature changes on pCO2 were small, with their contributions to the monthly medians of diurnal pCO2 variability being up to 12 and 5 µatm, respectively. During upwelling events, short-term pCO2 variability (up to 500 µatm within a day) largely exceeded the usual diurnal cycle. If the net annual air–sea flux of carbon dioxide at our study site and for the sampled period is calculated based on a data subset that consists of only one regular measurement per day, the bias in the net exchange depends on the sampling time and can amount up to ±12 %. This finding highlights the importance of continuous surface pCO2 measurements at fixed locations for the assessment of the short-term variability of the carbonate system and the correct determination of air–sea CO2 fluxes.